A cross-sectional analysis of schistosomiasis case detection by rectal mucosal biopsy among patients attending the digestive endoscopy unit of the internal medicine department - Kaly Keïta; Stéphane Loique Djeugoué; Boua Daoud Camara; Alassane Alfousséni Doumbia; Cheick Oumar Kamissoko; Oumar Sandji; Adama Sinayoko; Abdoulaye Keïta; Maïmouna Togo; Charles Dara; Garan Dabo; Abdoulaye Mamadou Traoré; et al. (Journal of Interventional Epidemiology and Public Health)
Introduction: The detection of schistosome eggs in stool or urine specimens is the most used technique in population-based studies, while the rectal mucosal biopsy is the commonly used technique in hospital setting. The aim of this hospital-based study was to describe the epidemiological aspects of schistosomiasis.